Efektivitas Pemberian Afirmasi Positif pada Mahasiswa Keperawatan yang mengalami Stres Akademik (Window of Nursing Journal, 2025)
Academic stress can be reduced with positive affirmations that can affect the subconscious and stimulate endorphins in the body so as to reduce academic stress. The purpose of this study was to determine the effect of positive affirmations on academic stress in students.This research is a quantitative study using a quasi-experimental design with a twogroup pre-posttest design approach. Samples were taken from populations that met the inclusion criteria in the Nursing Study Program, Faculty of Public Health, Indonesian Muslim University Makassaras many as 34 respondents by purposive sampling. The independent variable is Positive Affirmation while the dependent variable is academic stress.The results of this study showed that before the positive affirmations were carried out, 17 students served as the intervention group and 17 students served as the control group. the results of the Wilcoxon statistical test with a value of þ = 0.000 < α = 0.05, which means that there is a positive effect of affirmation on academic stress in this study it can be concluded that there is a positive effect of affirmation on reducing academic stress in nursing students at the Faculty of Public Health, Indonesian Muslim University. It is hoped that students will use positive affirmations as a coping mechanism of choice to deal with academic stress.